Effect to the Surface Composition in Ultrasonic Vibration-Assisted Grinding of BK7 Optical Glass - Pei Yi Zhao; Ming Zhou; Xian Li Liu; Bin Jiang (Applied Sciences, 2020)
Because of the changes in cutting conditions and ultrasonic vibration status, the proportion of multiple material removal modes are of uncertainty and complexity in ultrasonic vibration-assisted grinding of optical glass. Knowledge of the effect of machined surface composition is the basis for better understanding the influence mechanisms of surface roughness, and also is the key to control the surface composition and surface quality. In the present work, 32 sets of experiments of ultrasonic vibration-assisted grinding of BK7 optical glass were carried out, the machined surface morphologies were observed, and the influence law of machining parameters on the proportion of different material removal was investigated. Based on the above research, the effect of surface composition was briefly summarized. The results indicated that the increasing of spindle rotation speed, the decreasing of feed rate and grinding depth can improve the proportion of ductile removal. The introduction of ultrasonic vibration can highly restrain the powdering removal, and increase the proportion of ductile removal. Grinding depth has a dominant positive effect on the surface roughness, whereas the spindle rotation speed and ultrasonic amplitude both have negative effect, which was caused by the reduction of brittle fracture removal.